Compacting and partitioning‐based simulation solution for frequency‐dependent network equivalents in real‐time digital simulator. Issue 16 (1st December 2015) - Hu, Yizhong; Wu, Wenchuan; Zhang, Boming
Abstract : Rational models of frequency‐dependent network equivalents (FDNEs) have been used in real‐time digital simulator (RTDS) for power‐system simulation. However, this can lead to a computational burden issue; the application of FDNEs may result in a loss of real‐time simulation features because the computational cost of the FDNE component exceeds the limits of RTDS. The authors describe a solution that combines compacting and partitioning of the FDNEs, whereby the former reduces the redundancy in the mathematical model and the latter allows us to exploit parallel computer architectures. Then they describe the results of numerical simulations that demonstrate the effectiveness of the approach. Moreover, the proposed simulation solution is not limited to the applications of FDNEs in RTDS, it solves a set of subsistent computational issues when apply rational models in real‐time electromagnetic transients programs tools.